Hemorrhage glioblastoma mimicks a dural-based meningioma - Tse-Fu Wen; Lin-Hsue Yang; Che-Kuang Lin (Formosan Journal of Surgery, 2018)
The so-called “dural tail sign” (DTS) is a thickening of the dura that is most often seen adjacent to a meningioma. Although the DTS is highly specific for meningioma, it has been observed in numerous other intracranial lesions. The origin of the DTS is an issue of debate. Some authors have described it as a tumor extension, while others have considered it as a proliferation of connective tissue, hypervascularity, and vascular dilatation within the dura and adjacent to cranial masses. Here, we reported a rare case of glioblastoma multiforme (GBM) with image findings of a DTS. A 74-year-old female was taken to our hospital due to the sudden onset of mental status change and right-side hemiparesis. Brain magnetic resonance imaging (MRI) with contrast enhancement showed an intracranial mass with heterogeneous enhancement in the left temporal lobe which was consistent with the DTS. A left frontotemporal craniotomy was performed, and grossly total tumor removal was achieved. The final pathology reported was GBM. Although it is rare, GBM may also on occasion be associated with a DTS. The histopathological examination for DTS in GBM is limited. Currently, excision of the dural tail in GBM is suggested.